Decomposing the Motivation to Exert Mental Effort. (August 2021) - Shenhav, Amitai; Prater Fahey, Mahalia; Grahek, Ivan
Achieving most goals demands cognitive control, yet people vary widely in their success at meeting these demands. Although motivation is known to be fundamental to determining success at achieving a goal, what determines motivation to perform a given task remains poorly understood. Here, we describe recent efforts toward addressing this question using the expected-value-of-control model, which simulates the process by which people weigh the costs and benefits of exerting mental effort. This model functionally decomposes this cost-benefit analysis and has been used to fill gaps in understanding of the mechanisms of mental effort and to generate novel predictions about the sources of variability in real-world performance. We discuss the opportunities the model provides for formalizing hypotheses about why people vary in their motivation to perform tasks, as well as for understanding limitations in researchers' ability to test these hypotheses using a given measure of performance.